Generation and Assessment of Soybean (Glycine max (L.) Merr.) Hybrids for High-Efficiency Agrobacterium-Mediated Transformation - Muhammad Waqar Khan; Aaqib Shaheen; Xuebin Zhang; Junli Zhang; Yaser Hassan Dewir; Katalin Magyar-Tábori (Life)
The Agrobacterium-mediated technique is widely employed for soybean transformation, but the efficiency of this method is still relatively modest, in which multiple factors are involved. Numerous chemical and physiological cues from host plants are needed for A. tumefaciens attraction and subsequent T-DNA integration into the plant genome. Susceptible genotypes may permit this attachment and integration, and the agronomically superior genotypes with susceptibility to A. tumefaciens would play an important role in increasing transformation efficiency. In this study, we aimed to elevate the Agrobacterium-mediated transformation efficiency of soybean by integrating susceptibility alleles from William82 and flavonoids accumulating alleles from LX genotypes in the same soybean line. The crossing was made between LX () and William82 () soybean by hand pollination. Expectedly, the resulting hybrid soybean progenies inherited susceptibility traits and high flavonoid contents (i.e., genistein, genistin, apigenin, naringenin, quercetin, and cinnamic acid) essential for potential plant–pathogen interaction. Furthermore, the progenies and susceptible William82 soybean were subjected to transformation using A. tumefaciens (GV3101) harboring the GmUbi-3XFlag-35S-GFP and reassembled GmUbi3XFlag-35S-GFP: GUS vectors during separate events. Important transformation-related traits like shoot induction and shoot regeneration ability were also significantly improved in progenies. The progenies designated as ZX-3 exhibited superiority over the William82 parental line in all three traits, i.e., shoot induction, regeneration, and Agrobacterium-mediated transformation. The transient transformation efficiency of the ZX-16 line was remarkably higher when half-cotyledon explants were wounded and transformed with A. tumefaciens harboring GUS assembly vector and then co-cultivated on MS medium supplemented with 2 mg/L spermidine, 0.3 g/L GA3, 0.3 mg/L kinetin, and 1.3 mg/L 6-benzylaminopurine. In addition, the shoot elongation was also higher than that of William82 after two weeks of culture on the shoot induction medium. The newly generated soybeans have the potential to serve as a valuable source for high transgene production and represent a promising avenue for future soybean varietal development.